Exercise intensity and markers of inflammation during and after (neo-) adjuvant cancer treatment. Issue 3 (March 2021) - Schauer, Tim; Mazzoni, Anne-Sophie; Henriksson, Anna; Demmelmaier, Ingrid; Berntsen, Sveinung; Raastad, Truls; Nordin, Karin; Pedersen, Bente K; Christensen, Jesper F
Abstract : Exercise training has been hypothesized to lower the inflammatory burden for patients with cancer, but the role of exercise intensity is unknown. To this end, we compared the effects of high-intensity (HI) and low-to-moderate intensity (LMI) exercise on markers of inflammation in patients with curable breast, prostate and colorectal cancer undergoing primary adjuvant cancer treatment in a secondary analysis of the Phys-Can randomized trial (NCT02473003). Sub-group analyses focused on patients with breast cancer undergoing chemotherapy. Patients performed 6 months of combined aerobic and resistance exercise on either HI or LMI during and after primary adjuvant cancer treatment. Plasma taken at baseline, immediately post-treatment and post-intervention was analyzed for levels of interleukin 1 beta (IL1B), IL6, IL8, IL10, tumor-necrosis factor alpha (TNFA) and C-reactive protein (CRP). Intention-to-treat analyses of 394 participants revealed no significant between-group differences. Regardless of exercise intensity, significant increases of IL6, IL8, IL10 and TNFA post-treatment followed by significant declines, except for IL8, until post-intervention were observed with no difference for CRP or IL1B. Subgroup analyses of 154 patients with breast cancer undergoing chemotherapy revealed that CRP (estimated mean difference (95% CI): 0.59 (0.33; 1.06); P   = 0.101) and TNFA (EMD (95% CI): 0.88 (0.77; 1); P   = 0.053) increased less with HI exercise post-treatment compared to LMI. Exploratory cytokine co-regulation analysis revealed no difference between the groups. In patients with breast cancer undergoing chemotherapy, HI exercise resulted in a lesser increase of CRP and TNFA immediately post-treatment compared to LMI, potentially protecting against chemotherapy-related inflammation.